2020
DOI: 10.1186/s12964-020-00598-7
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus infection promotes the formation of glioma stem cells from glioblastoma cells through the TLR9/NEAT1/STAT3 pathway

Abstract: Background: Glioma stem cells (GSCs) are glioma cells with stemness and are responsible for a variety of malignant behaviors of glioma. Evidence has shown that signals from tumor microenvironment (TME) enhance stemness of glioma cells. However, identification of the signaling molecules and underlying mechanisms has not been completely elucidated. Methods: Human samples and glioma cell lines were cultured in vitro to determine the effects of adenovirus (ADV) infection by sphere formation, RT-qPCR, western blott… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…GSEA analysis showed that HMGB1 upregulated pluripotency-related genes in GBM cells ( Supplementary Figures 1C,D ), consistent with previously reports (Zang et al, 2020 ). We then cultured GBM cells with different concentrations of HMGB1, and determined the formation of tumor spheres under the neural sphere culture condition.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…GSEA analysis showed that HMGB1 upregulated pluripotency-related genes in GBM cells ( Supplementary Figures 1C,D ), consistent with previously reports (Zang et al, 2020 ). We then cultured GBM cells with different concentrations of HMGB1, and determined the formation of tumor spheres under the neural sphere culture condition.…”
Section: Resultssupporting
confidence: 91%
“…HMGB1, a well-known DAMP released by damaged cells, is reported to upregulate pluripotency-related genes in GBM cells (Zang et al, 2020 ). We then asked whether TMZ treatment could promote the expression of HMGB1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevant signal pathways include TLRs signal pathway, NK cell mediated cytotoxicity signal pathway and JAK-STAT signal pathway. TLRs signal pathway involves MYD88dependent or non-dependent mediations, former process stimulates proliferation in gliomas by inducing overexpression of proin ammatory factors 24,25 ; HLA-A existed in NK cell mediated cytotoxic signal pathway mainly encodes mammalian histocompatibility antigen, which could inhibit the antigen recognition process, reduce the immune response and cytotoxicity, and nally enhances tumor cell immune escape 26,27 ; JAK-STAT signal pathway and STAT3 were related to the release of antiin ammatory cytokines and the immunosuppressive environment in glioma, and participated in cell proliferation, differentiation, in ammation and tumorigenesis 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…OCT4 is a stemness-related transcription factor, which regulates the expression of both the lncRNAs NEAT1 and MALAT1 to promote the progress of lung cancer [ 28 ]. Moreover, NEAT1 leads to stem-like phenotypes in NSCLC, TNBC, and GBM cells [ 29 , 30 , 31 ]. The lncRNA B4GALT1-AS1 recruits the yes-associated protein (YAP) to the nucleus, a potent oncogene related to several oncogenic programs, including stemness.…”
Section: Introductionmentioning
confidence: 99%